Redistribution of sputtered material in a plane ion-plasma system with an abnormal glow discharge - Kuzmichev, A.I.; Melnichenko, M.S.; Shinkarenko, V.G.; Shulaev, V.M. (Вопросы атомной науки и техники, 2020)
The redistribution of the flow of sputtered material of a target (cathode) between the collector and the target in a plane–parallel electrode system with an anomalous glow discharge is analyzed in the kinetic approximation. Sputtering is the result of bombardment of the target by gas ions accelerated in the near–cathode space charge layer and by fast neutral atoms formed as a result of resonant ion charge exchange. Sputtered atoms partially return to the target due to collisions with gas molecules. The formulas were obtained, which were confirmed in the experiment that makes it possible to correctly estimate the ratio of the sputtered material flows deposited on the collector and the target. The results of the work are used to calculate the parameters of the processes of coating deposition and ion cleaning of the target under conditions of the anomalous glow discharge.